Enhancing Nutrient Intake, Digestibility, Rumen Fermentation, and Blood Metabolites in Kacang Goats Using Compost-Enriched Hydroponic Maize Fodder - Sulistijo, E. D.; Benu, I.; Oematan, G.; Rosnah, U. S.; Hilakore, M. A.; Jelantik, I. G. N. (Tropical Animal Science Journal, 2024)
This study aimed to enhance nutrient intake, digestibility, rumen fermentation, and blood metabolites in Kacang goats by substituting grass silage with hydroponic maize fodder enriched with fermented compost tea. The compost tea, prepared by fermenting organic compost with sugared water + 40 mL EM4 for 3 days, was used to grow maize fodder hydroponically. Four male Kacang goats (13.05 ± 1.32 kg) were assigned to four dietary treatments in a 4x4 latin square design over four 15-day periods (10 days for adaption, 5 days for data collection). The treatments were: 60% grass silage + 10% Leucaena leucocephala + 30% concentrate (control, FCG0); 30% grass silage + 30% hydroponic maize fodder + 10% L. leucocephala + 30% concentrate (FCG1); 15% grass silage + 45% hydroponic maize fodder + 10% L. leucocephala + 30% concentrate (FCG2); and 60% hydroponic maize fodder + 10% L. leucocephala + 30% concentrate (FCG3). Goats on FCG3 had lower (p<0.05) dry matter intake (152.48 g/day) compared to FCG0 (226.83 g/day). Nutrient digestibility, including organic matter and crude fiber, improved (p<0.05) in FCG3 (77.21% and 66.12%) compared to FCG0 (76.62% and 52.27%). Total volatile fatty acids (VFA) increased in FCG3 (131.54 mM) compared to FCG0 (111.73 mM). However, no significant differences were observed in ruminal ammonia (NH₃-N), ruminal pH, or blood metabolites. In conclusion, substituting grass silage with hydroponic maize fodder enriched with fermented compost tea up to 75% of the diet improved digestibility and rumen fermentation without negatively affecting intake, digestibility, or blood metabolites in Kacang goats, suggesting its potential as an alternative feed. However, complete substitution (100%) reduced intake, indicating challenges at higher substitution levels.